Autonomy and moral deference. Issue 2 (2nd June 2017) - Cross, Ben
Abstract : The idea that a person might have a duty to defer to the moral judgments of others is typically something that arouses our suspicion, in ways that other kinds of deference do not. One explanation for this is the value of autonomy. According to this explanation, people have a duty to be autonomous, and any act of deferring to another person's moral judgement is not an autonomous action. Call this "the Autonomy Argument" against moral deference. In this article, I criticise the Autonomy Argument. I argue that, even if we accept that an act of moral deference can never be autonomous, those who believe that people have a duty to be autonomous must accept that acts of moral deference are morally necessary. This is because some people are incapable of becoming autonomous by themselves, and deferring to a moral expert is the only way they might ever become autonomous.